Structure-based optimisation of orally active & reversible MetAP-2 inhibitors maintaining a tight 'molecular budget'. Issue 21 (1st November 2020) - Hirst, David J.; Brandt, Martin; Bruton, Gordon; Christodoulou, Erica; Cutler, Leanne; Deeks, Nigel; Goodacre, Jonathan D.; Jack, Torquil; Lindon, Matthew; Miah, Afjal; Page, Kevin; Parr, Nigel; et al.
Graphical abstract: Abstract: Structure-based led optimisation of orally active reversible Methionine Aminopeptidase-2 (MetAP-2) inhibitors utilising a 'molecular budget' medicinal chemistry strategy is described. The key physicochemical parameters of target molecules (cLogP, molecular size and H-bond donor count) were monitored through straightforward and intuitive use of atom count and distribution. The balance between structure-based design and an awareness of the physicochemical properties of the compounds synthesised enabled the rapid identification of a potent molecule with good oral pharmacokinetic (PK) characteristics by making fewer, higher quality compounds. The resulting candidate quality molecule was validated in a mechanistic cellular assay and a rodent secondary immunisation model.